Representasi Nilai-nilai Edukasi dalam Netflix bagi Generasi Z - Murpratiwi, Nerissa Mutiara; Yusuf, Bagus Muhammad; Salenusa, Jeremy Putra Budi; Ifadah, Lilla Sesliya; , Vera Wijayanti (Edukasi IPS, 2022)
Various platform services for streaming have been developed in this day and age, including the very famous one today, namely, Netflix. Netflix is ​​a streaming service that provides various tv series, documentaries, and movies that have spread in 190 countries. In this case Netflix is ​​widely used as an entertainment medium. However, in this study, we will focus on the problem of how to represent the educational values ​​that can be obtained through Netflix in Generation Z. The research method used in this study is a qualitative research method. The results of the research that we got are that Netflix as a streaming service media can provide educational values ​​such as the morals of life, language, and technology from the country the film/series is produced in, the meanings contained in the films/series they watch, as well as what influence is exerted through it. films/series provided by Netflix to Generation Z.    Abstrak Berbagai layanan platform untuk menonton secara online telah banyak dikembangkan pada zaman sekarang, termasuk yang sangat terkenal saat ini yaitu, Netflix. Netflix merupakan layanan streaming yang menyediakan berbagai tv series, documenter, dan film yang telah tersebar di 190 negara. Dalam hal ini Netflix banyak digunakan sebagai media hiburan. Namun, pada penelitian kali ini kami akan memfokuskan permasalahan pada bagaimana representasi nilai-nilai edukasi yang bisa didapatkan melalui Netflix pada generasi Z. Metode penelitian yang digunakan pada penelitian ini adalah metode penelitian kualitatif. Hasil penelitian yang kami dapatkan adalah Netflix sebagai media layanan streaming dapat memberikan nilai edukasi seperti bahasa dan budaya dari negara  film/series itu diproduksi, makna-makna yang terkandung dari film/series yang mereka tonton, serta pengaruh apa yang diberikan melalui fillm/series yang disediakan oleh Netflix kepada generasi Z.